One-pot encapsulation of lactate dehydrogenase and Fe3O4 nanoparticles into a metal–organic framework: A novel magnetic recyclable biocatalyst for the synthesis of D-phenyllactic acid - Sun, Xiaolong; Hu, Jiahuan; Wang, Yifeng; Luo, Xi; Huang, He; Fu, Yongqian (Frontiers in Bioengineering and Biotechnology, 2023)
The main challenges in bio-catalysis of D-phenyllactic acid (D-PLA) are poor tolerance of lactate dehydrogenase (LDH) to harsh environmental conditions and inability to recycle the catalyst. A novel magnetic framework composite was prepared as solid support for the immobilization of enzymes via one-pot encapsulation in this study. LDH/MNPs@MAF-7 was synthesized by the one-pot encapsulation of both LDH and magnetic nanoparticles (MNPs) in MAF-7. The LDH/MNPs@MAF-7 showed stable biological activity for the efficient biosynthesis of D-PLA. The structure and morphology of LDH/MNPs@MAF-7 were systematically characterized by SEM, FT-IR, XRD, VSM, XPS, TGA and N2 sorption. These indicated that LDH/MNPs@MAF-7 was successfully synthesized, exhibiting enhanced resistance to acid and alkali, temperature and organic solvents. Furthermore, the bio-catalyst could be separated easily using a magnet, and the reusability was once considerably expanded with 80% of enzyme activity last after eight rounds of recycling. Therefore, LDH/MNPs@MAF-7 could be used as a potential biocatalyst for the biosynthesis of D-PLA due to its good stability and recovery properties.